2015
DOI: 10.5505/kjms.2015.59454
|View full text |Cite
|
Sign up to set email alerts
|

Complementary and Alternative Medicine Use in Lung Cancer Patients and Its Impact on the Quality of Life

Abstract: praying (89%), performing salat (95%), laughing (82%), visiting a neighbour (78%) and dancing (54%). The most preferred herbal approaches were linden tea (81%), green tea(74%), thyme(70%), sage (67%), and grape seed crust(67%). Most used nutritional approaches were fruits-vegetables-fi sh-chicken-yogurt (100%), carrots (98%), garlic (97%), pomegranat(93%), meat (92%), pastry and milky desserts (91%). The rationale for using complementary and alternative medicine were feeling psychologically relaxed (81%) and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
(22 reference statements)
0
1
0
2
Order By: Relevance
“…Literatürde GETAT kullanımının ülkenin coğrafi konumuna, etnik kökene, eğitime, sosyoekonomik faktörlere ve dini inanışlara göre farklılık göstermekte olduğu; batı ülkelerinde en sık multivitaminler, meditasyon, hipnoterapi, gevşeme egzersizleri ve aromaterapi kulanırken; doğu ülkelerinde bitkisel karışımların kullanıldığı belirtilmektedir (20). Çalışmada COVID-19 pandemi öncesinde, bireylerin en sık olarak nane, ıhlamur, limon ve D vitamini kullandığı, protein ağırlıklı beslendiği, yürüyüş yaptığı ve girişimsel olarakta hacamat yaptırdığı görülmüştür.…”
Section: Bulgularunclassified
See 1 more Smart Citation
“…Literatürde GETAT kullanımının ülkenin coğrafi konumuna, etnik kökene, eğitime, sosyoekonomik faktörlere ve dini inanışlara göre farklılık göstermekte olduğu; batı ülkelerinde en sık multivitaminler, meditasyon, hipnoterapi, gevşeme egzersizleri ve aromaterapi kulanırken; doğu ülkelerinde bitkisel karışımların kullanıldığı belirtilmektedir (20). Çalışmada COVID-19 pandemi öncesinde, bireylerin en sık olarak nane, ıhlamur, limon ve D vitamini kullandığı, protein ağırlıklı beslendiği, yürüyüş yaptığı ve girişimsel olarakta hacamat yaptırdığı görülmüştür.…”
Section: Bulgularunclassified
“…Gülgün ve Kaya'nın yapmış oldukları çalışmada katılımcıların en çok sırasıyla ıhlamur çayı, yeşil çay, kekik, adaçayı ve üzüm çekirdeği kullandığı, meyve-sebze-balık-tavuk-yoğurt, havuç, sarımsak, nar, hamur, sütlü tatlı ve kırmızı et tercih ettikleri belirlenmiştir (20). Çalışmanın literatürle kısmen uyumlu olduğu görülmektedir.…”
Section: Bulgularunclassified
“…13,[16][17][18][19][20][21] However, limited number of studies were found in investigating the use of herbal products in patients with diabetes in Turkey. 5,[22][23][24][25] It is important to know the herbal…”
Section: Introductionmentioning
confidence: 99%